Identifikasi Bakteri Patogen Gram Negatif pada Alat Praktikum Mikrobiologi di Laboratorium Central Stikes Maharani Malang - Vita Ainun Vita Ainun; Erni Yohani Erni Yohani; Yeni Avidhatul Yeni Avidhatul (Journal Borneo, 2024)
Stacks of laboratory equipment and lack of routine sterilization can contribute to the growth and contamination of pathogenic bacteria. This research aimed to determine the types of gram-negative pathogenic bacteria present in the microbiology practicum equipment at the Central STIKes Maharani Malang Laboratory. This type of research is descriptive research with an analytical research design. The sampling technique uses purposive sampling. This research involves taking swab samples on the surface of practical microbiology equipment, isolating bacterial colonies using MCA (Mac Conkey Agar) media, making pure cultures on MCA slanted agar media, macroscopic observations, and biochemical tests. Bacteria were grown on MCA media for 2x24 hours. The results of research using gram staining showed gram-negative bacteria, rod-shaped, spread, and red. Biochemical tests showed glucose (+g), lactose (+), mannitol (+), maltose (+), sucrose (+), H2S (-), indole (-), Mr (Methyl Red) (-), Vp ( Voges Praskaeur) (+), citrate (+), motility (-), the bacterial species Klebsiella pneumoniae was found. The second result shows glucose (+g), lactose (+), mannitol (+), maltose (+), sucrose (+), H2S (-), indole (+), Mr (Methyl Red) (+), Vp ( Voges Praskaeur) (-), citrate (-), motility (-), found Escherichia coli bacterial species. This study concluded that it was found that gram-negative bacteria were rod-shaped, spread, and red. Meanwhile, from biochemical tests using glucose, lactose, mannitol, maltose, sucrose, ındol, MR, VP, and citrate, Klebsiella pneumoniae and Escherichia coli bacteria were found.